Effect of Baduanjin Sequential Therapy on the Quality of Life and Cardiac Function in Patients with AMI After PCI: A Randomized Controlled Trial. (4th July 2020) - Chen, Ming-Gui; Liang, Xuefei; Kong, Lili; Wang, Jingjing; Wang, Fangfang; Hu, Xiyan; He, Jianzhuo; Zeng, Rui-Xiang; Mao, Shuai; Guo, Liheng; Zhang, Min-Zhou; Zhang, Xiaoxuan
Abstract : Purpose . The purpose of this study was to examine the effects of Baduanjin sequential therapy (BST) on the quality of life and cardiac function in patients with AMI after PCI. Subjects. 96 patients with AMI after PCI were randomly assigned as subjects to two groups: BST group who received 24 weeks of BST training and control group who received no training. Methods . The methods used in this study included the changes in SF-36 subscales, the measures of left ventricular ejection fraction (LVEF), N-terminal pro-B-type natriuretic peptide (NT-pro-BNP), the body mass index (BMI), and the abdominal circumference. Results . Of the 96 participants, 82 total patients completed the entire study. At 12 weeks, role physical and health transition of SF-36 were significantly different between the two groups, with a difference of 26.12 (95% CI, 11.59 to 40.64) in role physical and a difference of 15.94 (95% CI, 5.60 to 26.28) in health transition (p < 0.05 ). However, there were statistically significant differences in all aspects of SF-36 between the two groups at 24 weeks (p < 0.05 ). The BST also lowered abdominal circumference and BMI as compared with the control group. In the 24-week follow-up, a significant difference was found in the decline of the LVEF in the control group (p = 0.020 ), while there was a nonsignificant difference in the BST group (p = 0.552 ). Compared with the control group, the BST group reduced 50 pg/ml on the NT-pro-BNP at 24 weeks (p = 0.013 ). The effects of BST exercise were maintained at 24 weeks after the intervention. No serious adverse events were observed. Conclusions . The BST appears to improve the quality of life in patients with AMI after PCI, with additional benefits of lowered abdominal circumference and BMI and improved level of cardiac function. This trial is registered with NCT02693795 .